The Role of Patronage in Shaping Indonesia's Political Landscape - Annisa, Silvia; Situmorang, Bonar (Departemen Sosiologi Universitas Gadjah Mada, 2024)
This article presents a systematic literature review on the role of patronage in shaping Indonesia's political landscape. Using a systematic literature review approach, the article analyzes 30 selected articles out of a total of 250 articles that underwent identification and screening processes. The main focus of this review is to explore how political patronage influences power structures, political participation, and the dynamics of relations between political elites and the public in Indonesia. Drawing on Michel Foucault's theory of power and knowledge, the article explores how patronage not only functions as a tool for distributing resources but also plays a crucial role in the construction and dissemination of political knowledge. According to Foucault, power is not just imposed from above but operates through networks of relationships, shaping the way knowledge is produced and legitimized. Patronage systems produce specific truths that validate the power structures and create a discourse that legitimizes inequality and exclusion. The findings suggest that patronage remains an essential tool in political mobilization, influencing both the distribution of resources and the strengthening of social and political networks. However, the complexity of patronage also poses challenges for the development of an inclusive and transparent democracy. This article provides a deeper understanding of the influence of patronage in Indonesian politics, offering insights for the development of more just and sustainable political policies, while reflecting on Foucault’s ideas about how knowledge and power intertwine to shape political realities.